Development of promotion of palm starch products based on information technology - Andi Widiyanto; Dwi Chandra Adi Prabowo; Naufal Hanif Albahi; Dandi Karunia Pratama; Indah Kristiana; Wahyu Adhitya (Community Empowerment, 2023)
Tuksongo Village, Borobudur District, has been a palm starch center since 1992. However, MSME palm starch was only founded a few years ago. The problem faced by partners is the absence of product marketing, social media accounts and online sales applications, so product sales are still focused on the local area. This program is an effort to increase product sales with digital marketing. Activities are carried out in the form of digital marketing training with social media and website development for marketing and selling products. The result of this program is that partners who have knowledge about digital marketing can apply it to promote the products they produce. Apart from that, social media accounts and websites are also produced which are used by partners as a means of promotion and online sales.